Community Perceptions of Tourism in Small Island States: A Conceptual Framework - Nunkoo, R.; Ramkissoon, Haywantee (Routledge, 2010)
Sustainable tourism development is a major challenge for small island economies. Yet, little research has been conducted on the social implications of tourism development and their role in the sustainable development of such economies. This research discusses the importance of understanding community perceptions of tourism development in small island states by proposing a theoretical framework based on social exchange theory. The framework defines attitudes to tourism as the residents’ perceptions toward the positive and negative impacts of tourism, which in turn influence support for the industry. The model also proposes that the independent variables influencing attitudes to tourism are economic dependence on the industry, occupational identity, community attachment, and level of power. The state of the local economy is given as a moderating variable between dependence on the industry and the perceived positive and negative impacts. The relationship between level of power and perceived positive and negative impacts is considered to be moderated by the gender of the residents. The policy implications of adopting such a model are discussed.